Lexical Hedges in Female Speech: An Analysis of Contemporary Talk Show - Safdar, Mahnoor; Mahmood, Urooj; Rehman, Amina (Pakistan Languages and Humanities Review, 2024)
The study elaborates the use of lexical hedges specifically in female speech. The focus was on finding frequently used lexical hedges in female speech and to analyze the impact of these lexical hedges in their communication style. However, the qualitative analysis of Anupama Chopra’s talk show was conducted. To analyze the female speech pattern in the said show, Martin’s (2008) two strategies of indetermination and subjectivization acted as the theoretical framework of the study at hand. Based on this research, it has been deduced that women tend to use “You know” in a greater number as compared to other lexical hedges. Additionally, the more lexical hedges women use, the more their speech become incoherent and unclear. Moreover, the study recommends to draw the results of frequency of lexical hedges in the day to day conversation of females using the frequency formula.